A Mutant of Arp2p Causes Partial Disassembly of the Arp2/3 Complex and Loss of Cortical Actin Function in Fission Yeast - Morrell, Jennifer L. (The American Society for Cell Biology, 1999)
The Arp2/3 complex is an essential component of the yeast actin cytoskeleton that localizes to cortical actin patches. We have isolated and characterized a temperature-sensitive mutant of Schizosaccharomyces pombe arp2 that displays a defect in cortical actin patch distribution. The arp2(+) gene encodes an essential actin-related protein that colocalizes with actin at the cortical actin patch. Sucrose gradient analysis of the Arp2/3 complex in the arp2-1 mutant indicated that the Arp2p and Arc18p subunits are specifically lost from the complex at restrictive temperature. These results are consistent with immunolocalization studies of the mutant that show that Arp2-1p is diffusely localized in the cytoplasm at restrictive temperature. Interestingly, Arp3p remains localized to the cortical actin patch under the same restrictive conditions, leading to the hypothesis that loss of Arp2p from the actin patch affects patch motility but does not severely compromise its architecture. Analysis of the mutant Arp2 protein demonstrated defects in ATP and Arp3p binding, suggesting a possible model for disruption of the complex.